Mythological aspects of the kyrgyzs’ ethnographic way of life in the historical epos “Manas” - Seiilbek, Saken; Sarbassov, Bolatkhan; Ismakova, Aigul; Pirali, Gulziya; Ibraemova, Jansaya (Opción, 2018)
Myths existed at Kyrgyz as well as at many people of the world. Folklore of Kyrgyz people is multigame and is one of an important oral works are myths. They make part of spiritual culture of mankind and have survived to our day as the most ancient basis in the world literature. Considerable part of mythological plots of the epos ―Manas‖ makes narrations about animals which names are used as comparisons in many cases. They are important historical and ethnographic information on antecedents of the Kyrgyz. We can tell that the hero of epos ―Manas‖ is associated with the Kyrgyz people.